Pemilihan Universitas Favorit dengan Pendekatan Rantai Markov - Nursanti, Tinjung Desy; Irianti, Laksmi Sito Dwi; Sarjono, Haryadi (Bina Nusantara University, 2010)
The purpose of this study was to determine the amount of transfer of interest at class XII students in a private high school in Bogor to five universities in the Greater Jakarta namely UI, UBinus, Untar, IPB and UPH in the next period and the conditions of equilibrium, and to discover the source of reference selection and assessment of students on the fifth university. Sample consists of 411 class XII students in a private high school in Bogor, with the method and type of survey research is descriptive research. The result is a prediction of the five university in order in the next period of (0.22, 0.31, 0.14, 0.22, 0.11) when the equilibrium prediction of (0.15, 0.562, 0.076, 0.151, 0.09) and the selection of a reference source that is 29% of promotional events, 25 % of the ads, 24% of the families, and 22% from friends. Largest market share held by UBinus enthusiasts of 56.2%, while the smallest market share owned by Untar enthusiasts that is equal to 7.6%.Â